Freimaurertum bei Puškin Einfuehrung in die russische Freimaurerei und ihre Bedeutung fuer Puškins literarisches Werk - Wolf, Markus (Slavistische Beitraege, 1997)
In the series Slavonic Contributions Slavic dissertations of German-speaking countries as well as occasionally also American, English and Russian are published. In addition, the series provides a forum for anthologies and monographs of established scientists.